2022
DOI: 10.1161/circulationaha.121.056072
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of DANISH (The Danish Study to Assess the Efficacy of ICDs in Patients With Nonischemic Systolic Heart Failure on Mortality)

Abstract: Background: The Danish Study to Assess the Efficacy of Implantable Cardioverter-Defibrillators (ICDs) in Patients with Non-ischemic Systolic Heart Failure on Mortality (DANISH) found that primary-prevention ICD implantation was not associated with an overall survival benefit in patients with non-ischemic systolic heart failure during a median follow-up of 5.6 years, though there was a beneficial effect on all-cause mortality in patients ≤70 years. This study presents an additional four years of fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…In contrast, the recent ESC guideline has degraded its recommendation to class IIa 1. The basis for this contentious issue is that the recent The Danish Study to Assess the Efficacy of Implantable Cardioverter-Defibrillators in Patients with Non-ischemic Systolic Heart Failure on Mortality trial revealed that ICD implantation for primary prevention did not substantially reduce all-cause mortality risk in patients with NICM after a median follow-up of 9.5 years 33. Aside from the previously stated stretch-induced arrhythmia mechanism, scar formation resulting from a prior myocardial infarction can also result in ventricular tachyarrhythmias in patients with HF, implying that NT-pro BNP as a parameter of ventricular dilatation may not be solely correlated with appropriate ICD shock in patients with ICM 34.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the recent ESC guideline has degraded its recommendation to class IIa 1. The basis for this contentious issue is that the recent The Danish Study to Assess the Efficacy of Implantable Cardioverter-Defibrillators in Patients with Non-ischemic Systolic Heart Failure on Mortality trial revealed that ICD implantation for primary prevention did not substantially reduce all-cause mortality risk in patients with NICM after a median follow-up of 9.5 years 33. Aside from the previously stated stretch-induced arrhythmia mechanism, scar formation resulting from a prior myocardial infarction can also result in ventricular tachyarrhythmias in patients with HF, implying that NT-pro BNP as a parameter of ventricular dilatation may not be solely correlated with appropriate ICD shock in patients with ICM 34.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no evidence of a heterogeneity in ICD effectiveness depending on the presence of a CRT. 14 The lack of benefit with primary prevention ICD was subsequently confirmed in a long-term follow-up of the DAN-ISH trial patients (median 9.5 years), 76 as well as in a subgroup of patients with non-ischaemic HFrEF form the SCD-HeFT trial, followed for a median of 11 years. 77 However, the original DAN-ISH trial did show a significant risk reduction in all-cause and cardiovascular mortality in patients <70 years of age, 15 which was maintained over an extended follow-up.…”
Section: Role Of Implantable Cardioverter-defibrillatorsmentioning
confidence: 94%
“…The DANISH trial results, 19 preceded by SCDHEFT and DEFINITE, put in discussion the effects on global survival after ICD implantation in patients with non-ischaemic DCM heart failure and ejection fraction ≤35%, despite acknowledging the significant impact on SCD among younger patients. In the latest 2022 ESC guidelines, according to these results, primary prevention ICD implantation in non-ischemic DCM grade of recommendation was lowered from IA to IIa-A; it must be underlined, although, that subgroups at high risk of SCD exist, and the indication to implantation should be individually evaluated and tailored on the patient.…”
Section: Arrhythmic Risk Assessmentmentioning
confidence: 99%